2012
DOI: 10.1007/s10834-012-9317-0
|View full text |Cite
|
Sign up to set email alerts
|

Asset Ownership of New Asian Immigrants in the United States

Abstract: This study examined the asset ownership of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…Although not as prevalent as black-white household wealth studies, some research examines Asian and Latino wealth (Campbell and Kaufman 2006; Eller and Fraser 1995; Grant 2000; see also Jinhee Kim, Swarn Chatterjee, and Soo Hyun Cho 2012). Many of the same processes that contribute to black-white wealth inequality also disadvantage Latinos.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Although not as prevalent as black-white household wealth studies, some research examines Asian and Latino wealth (Campbell and Kaufman 2006; Eller and Fraser 1995; Grant 2000; see also Jinhee Kim, Swarn Chatterjee, and Soo Hyun Cho 2012). Many of the same processes that contribute to black-white wealth inequality also disadvantage Latinos.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Given the persistent racial/ethnic gap in many aspects of financial outcomes, there is a need to understand the causes of the differences. While minorities' ownership of asset‐building investments, such as the stock and housing market has not kept up with that of Whites (Hanna and Lindamood, 2008; Kim et al ., 2012), our understanding of the retirement saving motives held by various racial groups is not complete. Therefore, the purpose of this study is to investigate racial/ethnic differences in holding a retirement saving motive using the 2016 Survey of Consumer Finances (SCF).…”
Section: Introductionmentioning
confidence: 99%
“…Using the SCF, Letkiewicz and Hanna (2013) reported that Asians were less likely than Whites to meet the 25 % capital accumulation ratio guideline. Kim et al (2012) examined the asset ownership of Asian immigrants using the New Immigrant Survey. The authors found that ownership of a business or farm, financial assets, and home ownership differed across ethnic groups.…”
Section: Risk Tolerance and Investment Ownershipmentioning
confidence: 99%